Isoliquiritigenin inhibits TGF-β1-induced fibrogenesis through activating autophagy via PI3K/AKT/mTOR pathway in MRC-5 cells. (8th July 2020) - He, Jinjuan; Peng, Hao; Wang, Meifang; Liu, Ying; Guo, Xingrong; Wang, Bin; Dai, Longjun; Cheng, Xueqin; Meng, Zhongji; Yuan, Leyong; Cai, Fenglin; Tang, Yijun
Abstract: Isoliquiritigenin (ISL), a natural flavonoid derived from the root of liquorice, has been reported to possess anti-inflammatory and antioxidant activities. Previous studies have found that ISL plays a crucial role in anti-fibrosis of adipose tissue and renal tissue; however, its effect on pulmonary fibrogenesis has not been demonstrated. In this study, we aimed to explore the roles and the underlying mechanisms of ISL in TGF-β1-induced fibrogenesis using human lung fibroblast-derived MRC-5 cells. Cell proliferation and migration were determined by MTT and wound healing assay, respectively. The expression levels of alpha-smooth muscle actin (α-SMA), collagen type I alpha 1 (COLIA1) and fibronectin (FN), microtubule-associated protein light chain 3 (LC3) and related signaling molecules were detected by quantitative real-time PCR, western blot and immunofluorescence assay, correspondingly. EGFP-LC3 transfection was used for autophagy analysis. The results showed that ISL inhibited the TGF-β1-induced proliferation and migration, and down-regulated the expressions of α-SMA, COLIA1 and FN. ISL treatment led to up-regulation of LC3 in TGF-β1-treated MRC-5 cells, accompanied by significant decrease in the phosphorylation levels of phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT), and mammalian target of rapamycin (mTOR). In addition, the inhibitory effects of ISL on TGF-β1-induced fibrogenic features in MRC-5 cells were enhanced by pretreatment with autophagy activator Rapmycin and PI3K/AKT inhibitor LY294002 and reversed by autophagy inhibitor 3-methyladenine and PI3K/AKT activator IGF-1. Taken together, our results demonstrated that ISL could attenuate the fibrogenesis of TGF-β1-treated MRC-5 cells by activating autophagy via suppressing the PI3K/AKT/mTOR pathway. Therefore, ISL holds a great potential to be developed as a novel therapeutic agent for the treatment of pulmonary fibrosis.